Outcome of pregnancy in gestational diabetes as compared to overt diabetes - Banker, Chirag R.; Mehta, Latika R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Diabetes mellitus is a chronic metabolic disorder characterised by polyuria, polyphagia, polydipsia and glycosuria. Diabetes in pregnancy can be defined as pregestational (pre-existing) diabetes or gestational diabetes have type 1 (T1DM) or type 2 (T2DM) diabetes mellitus. Present study was carried to compare the maternal and perinatal outcome of overt diabetes mellitus as compared to gestational diabetes mellitus (PGDM) with that of gestational diabetes (GDM). Methods: An observational study was conducted at obstetrics and gynaecology department of a tertiary care center from July 2010 to October 2012 among 23 diabetic women. Seven of them were cases of overt diabetes while 16 were diagnosed during pregnancy. Maternal and fetal outcome were studied. All patients were followed from time of admission to discharge from hospital. Results: mean age of the participants were 26.71±4.89 in overt diabetes as compared to 27.56±4.41 among gestational diabetes. Illiteracy, low socio-economic status, rural residence, family history of diabetes was also high in overt diabetes mellitus as compared to GDM but none of them was statistically significant (P < 0.05). Intrauterine fetal death was more among GDM (37.5%) as compared to overt diabetes (28.57%). Prematurity and LBW were also high in overt diabetes as compared to GDM but none of them were statistically significant. Oligohydramnios, polyhydramnios and premature rupture of membrane were higher in gestational diabetes mellitus as compared to overt diabetes among women. Rate of LSCS were higher in gestational diabetes. Conclusions: Diabetes whether over or gestational is responsible for the poor outcome of the pregnancy so tight control is needed.